PHYTOPLANKTON DIVERSITY OF IN FOUR LAKES OF SATARA DISTRICT, MAHARASHTRA STATE - LEELA J. BHOSALE,; SUREKHA N. DHUMAL,; ANJALI B. SABALE, (The Bioscan, 2010)
The paper deals with occurrence and biodiversity of phytoplankton. Occurrence of phytoplankton in four lakes, namely, Mayani, Dhakani, Divad and Rajewadi (Dist. Satara) were investigated in the months July, August and December, 2009. In these lakes 68 species of phytoplankton and 13 species of filamentous algae were recorded belonging to five major classes of algae, namely, Cyanophyceae, Chlorophyceae, Euglenophyceae, Dinophyceae, and Bacillariophyceae. Further, Divad site was studied up to December 2009. It was found at Divad that the density of phytoplankton was, 1470, 1584 and 2741 cells/L in July, August and December, respectively. The class Chrysophyceae was represented in August. The species diversity index is very high because of the number of contributing species. Similarity index is determined to know seasonal variations.